Ženski pesemski diskurz v spletu povojnih ideologij - Balžalorsky Antić, Varja (Primerjalna književnost, 2019)
The paper is dedicated to the poetry book Shadow in the Heart by Ada Škerl. The year 2019 marks seventy years since the publication of this poetry collection which was in many respects a landmark and which has to date never been reprinted, and ten years since the death of this ignored author who had been marginalized for many years and who was rehabilitated only at the end of her life. Using the case of this poetry book, the paper pinpoints some of the tensions among different forms of ideology and women's poetic discourse in the period after World War II. It first outlines the position of women in the then society based on media images, and goes on to present the ideologically dictated poetry production of the time as well as the turn towards intimism. This is followed by a dense analysis of the book in terms of themes and motifs and a transnarratological analysis, with an emphasis on representations of social gender: we find that the discourse of these poems remains within the bounds of patriarchal structures in both the poetological sense and the sense of social gender. The second part of the paper discusses the book's negative reception and its long-term consequences (creative self-censorship, long-lasting stigmatisation and staying on the margins of the poetry canon). The final part tackles the reasons why Shadow in the Heart's ground-breaking role as the beginner of the intimist poetry current has not been acknowledged by literary history.
Keywords: intimizem; literarna recepcija; literarne študije; pesniški kanon; slovenska književnost; slovenska poezija; socialistična ideologija; Škerl, Ada: Senca v srcu; žensko pisanje